In vitro deletion mapping of the viral strand replication origin of Pseudomonas bacteriophage Pf3. - Luiten, R G (1991)
The origin of viral strand replication of the filamentous bacteriophage Pf3 has been characterized in Escherichia coli by in vitro deletion mapping techniques. The origin region was functionally identified by its ability to convey replicative properties to a recombinant plasmid in a polA host in which the replication origin of the vector plasmid is not functional. The origin of Pf3 viral strand replication is contained within a DNA sequence of 139 bp. This sequence covers almost completely one of the intergenic regions of the Pf3 genome, and it specifies both replication initiation and termination functions. Although no nucleotide sequence homology is present between the Pf3 origin of viral strand replication and that of the E. coli filamentous phages Ff (M13, f1, and fd) and IKe, their map positions and functional properties are very similar.